PEMBENTUKAN TEORI PERATURAN PERUNDANG-UNDANGAN - Michael Frans Berry (Universitas Muhammadiyah Metro, 2018)
Based on Law Number 12 of 2011, the meaning of statutory regulations is a written regulation that contains legally binding norms. Legislations which are formed and stipulated by state institutions or officials whose sequence is regulated in statutory regulations. Legislation in the form of written decisions, statutory regulations in the form of authorized officials, and statutory regulations that are binding in general, are not always binding but only show that these laws and regulations do not apply concretely or individually. Legislation theory is oriented towards seeking clarity and clarity of meaning and / or understandings and is cognitive in nature, legislation is a process and technique for the preparation of a set of legal regulations. Legislative powers correspond to a hierarchy of regulations. In the Elucidation of Article 7 paragraph 2 of Law Number 12 Year 2011, what is meant by hierarchy is the separation of each type of legislation. The ranking is based on the principle that lower regulations must not conflict with higher regulations. This principle is in accordance with the Stufen Theory or Ladder Theory of the jurist Hans Kelsen in General Theory of Law and State (1945). Legislation is a process of forming state regulations, both at the central and regional levels; and legislation as well as all state regulations is the result of the formation of regulations, both at the central level as well as at the regional level.